Knowledge and attitude toward physical restraint of older patients among nurses in Hospital Pakar Universiti Sains Malaysia (HPUSM) - Ismail, Ain Husniyyati (Universiti Sains Malaysia, 2025)
The use of physical restraints in healthcare settings, particularly for older adults, continues to raise ethical, psychological, and clinical concerns. Nurses play a pivotal role in the application and decision-making process related to physical restraints. This study aimed to assess the knowledge and attitudes of nurses toward the use of physical restraints for older patients in Hospital Pakar Universiti Sains Malaysia (HPUSM). A cross-sectional study design was employed, involving 120 registered nurses from medical and surgical wards. Data were collected using a self-administered questionnaire consisting of three sections: sociodemographic data, knowledge regarding physical restraints, and attitudes toward their use. Data were analysed using SPSS version 28.0. Descriptive statistics were used to determine the levels of knowledge and attitudes among nurses, while Pearson correlation was applied to explore the relationship between these two variables. The findings revealed that 49.2% of participants demonstrated a moderate level of knowledge, while 63.3% exhibited a neutral attitude toward the use of physical restraints. Pearson correlation analysis identified a statistically significant positive relationship between the level of knowledge and attitudes (r = 0.329, p = 0.001). Therefore, these findings highlights the need for continuous training to support more ethical nursing practices.